Strategic Strategy Sonok Culture in Efforts to Purify Madura Cattle: (case study in Waru Barat village, Pamekasan district) - MOH ZALI (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2019)
Sonok cow culture is a female Madura cow (mother) that is specially raised and raised for the purpose of pleasure through beauty, skill contests and has high economic value. Sonok cattle contest is a type of culture that has long existed and developed on Madura Island. The existence of this type of culture has given rise to a commitment and determination for the Madurese community, especially for fans of sonok cows and the local government to continuously purify Madurese cows as well as efforts to preserve tourism assets on Madura Island. The results of the study indicate that the strategy that can be used for the development of sonok cattle in the Sonok Cow Tourism Village of West Waru Village is in the first quadrant, namely, strength-opportunity (supporting aggressive strategies) with a coordinate point P (1.62; 2.47) which combines the strengths possessed by take advantage of opportunities in Waru Barat Village, Pamekasan Regency. The strategies that can be used are as follows (1) Making souvenirs or souvenirs from Madura and Sonok cattle education to become part of the tourism village of Sonok cattle. Supporting power such as the road to the village and the behavior of the village tourism sonok cattle that need to be fostered by related parties. (2) The existence of a display cattle gathering (taccek column) to attract tourists both local-regional and can improve the welfare of sonok cattle breeders through transactions that occur in the taccek column. (3) Madura specialty food sellers, especially Pamekasan, such as rujak cingur etc., are needed to spoil the visitor's tongue and become one of the good destinations.